1990
DOI: 10.1007/bf02251241
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin synthesis in rat and human substantia nigra

Abstract: A relation between neuromelanin synthesis and vulnerability of dopaminergic neurons is suggested by the fact that heavily pigmented cells are preferentially lost in aging and Parkinson's disease and that the dopaminergic neurotoxin MPP+ (1-methyl-4-phenyl-pyridine) binds to neuromelanin. To elucidate the mechanism of neuromelanin synthesis, we studied the formation of melanin in homogenates of human and rat substantia nigra tissue "in vitro". It was found that enzymatic processes accounted for 70% and 90% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Whether this is the predominant mechanism for neuromelanin formation in vivo is not known. However, in the absence of an identifiable enzyme in brain that catalyzes the oxidation of DA, it generally has been assumed that the process occurs spontaneously (Rodgers and Curzon, 1975;Graham, 1979 ;Rabey and Hefti, 1990) .…”
mentioning
confidence: 99%
“…Whether this is the predominant mechanism for neuromelanin formation in vivo is not known. However, in the absence of an identifiable enzyme in brain that catalyzes the oxidation of DA, it generally has been assumed that the process occurs spontaneously (Rodgers and Curzon, 1975;Graham, 1979 ;Rabey and Hefti, 1990) .…”
mentioning
confidence: 99%
“…Subsequently, it was found that DA also can form similar reactive compounds (Tse et al, 1976;Graham, 1978), and can exert neurotoxic effects both in vitro Moldéus et al, 1983 ;Michel and Hefti, 1990) and in vivo (Filloux and Townsend, 1993). The formation of these reactive metabolites can occur by one of the following three routes : (1) DA can undergo autoxidation by one or two electron transfers, a process accelerated by the presence of transition metal ions (Halliwell, 1992); (2) the brain can oxidize DA enzymatically (Grisham et al, 1987 ;Rabey and Hefti, 1990;Schipper et al, 1991), a process that can occur by several means, including via the peroxidase activity contained in prostaglandin synthase (Hastings and Zigmond, 1992); and (3) HZOZ is formed as a normal product of DA metabolism by monoamine oxidase and, without reduction by adequate GSH peroxidase, can be broken down through interaction with metal ions into free radical species such as OZ-or OH- (Maker et al, 1981 ;Halliwell, 1992). In short, conditions that increase concentration and/or turnover of DA should increase the potential for the formation of reactive metabolites through one or more of these routes .…”
mentioning
confidence: 99%
“…In contrast to that mechanism, during the last years there are some further lines of evidence indicating the involvement of different enzymes in o-diphenol oxidation and neuromelanin formation inside the nervous system. These enzymatic species, are tyrosine hydroxylase (Haavik, 1997), tyrosinase (Steel et al, 1992;Tief et al, 1996), prostaglandin H synthase/synthetase (Hasting, 1995;Mattammal et al, 1995), peroxidase (Carstam et al, 1991;Okun et al, 1971) and monoamine oxidase (Rabey and Hefti, 1990).…”
Section: Enzymatic Formation Of Neuromelaninmentioning
confidence: 98%